2019
DOI: 10.1111/anae.14858
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic benefits and clinical role of the posterior suprascapular nerve block in shoulder surgery: a systematic review, meta‐analysis and trial sequential analysis

Abstract: The posterior suprascapular nerve block has been proposed as an analgesic alternative for shoulder surgery based on the publication of several comparisons with interscalene block that failed to detect differences in analgesic outcomes. However, quantification of the absolute treatment effect of suprascapular nerve block on its own, in comparison with no block (control), to corroborate the aforementioned conclusions has been lacking. This study examines the absolute analgesic efficacy of suprascapular nerve blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…26 Indeed, we have come to realize that the posterior suprascapular block alone blocks only the posterior superior quadrant 26 of the shoulder joint, thus providing partial pain relief only. In fact, Cho et al 45 recently pooled the results of 10 trials comparing posterior suprascapular nerve block to placebo. Their meta-analysis revealed this block is only marginally better than placebo; and its analgesic effects on 24-h pain scores and opioid consumption were not clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…26 Indeed, we have come to realize that the posterior suprascapular block alone blocks only the posterior superior quadrant 26 of the shoulder joint, thus providing partial pain relief only. In fact, Cho et al 45 recently pooled the results of 10 trials comparing posterior suprascapular nerve block to placebo. Their meta-analysis revealed this block is only marginally better than placebo; and its analgesic effects on 24-h pain scores and opioid consumption were not clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study showed only modest improvement of the VAS score, with no improvement in other parameters of functional scores or health-related quality of life at 4-weeks of injections. A recent systematic review demonstrated that SSNB is statistically, but not clinically, superior to control for the area under curve of pain VAS score with a mean difference of 1.01 cm, suggesting that SSNB produced only modest improvements in analgesic outcomes [ 14 ]. Although this finding is similar to our study, we found that the proximal approach was superior in terms of identifying the nerve and the use of US guidance, thereby obviously improving the accuracy, as compared to SSNB using landmark-guided (blind) posterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…We received some comments from Drs Heesen and Klimek claiming to detect some discrepancies in our recent manuscript and questioning the findings. Below are the replies to their points.…”
mentioning
confidence: 99%